Pengaruh Lingkungan Kerja, Pelatihan dan Pemberdayaan SDM Terhadap Kinerja Karyawan - Desi Situngkir, Sri Pholan; Tiara, Tiara; Anggraini, Rahmania; Hidayati, Irma; Anggraini, Elisa; Ansyahri, Aldri (Teewan Journal Solutions, 2025)
This research discusses the influence of training, empowerment of human resources (HR), and work environment on employee performance. Through a systematic literature review (SLR) method that analyzes 18 journals, this research asks three research questions regarding the influence of this third factor on employee performance. The research results show that the work environment has a significant influence on employee performance, especially through job satisfaction as a mediator. Apart from that, training and empowerment of human resources also makes a positive contribution to performance. The work environment is divided into physical and non-physical, while training aims to improve employee knowledge and skills. Empowerment gives employees autonomy and confidence to innovate. This research suggests companies improve work environment training and achieve better employee performance, as well as the importance of the interaction between work stress, work environment, training and empowerment in influencing employee performance.